Using bilingual test to assess Malaysian limited English proficient students’ mathematics achievement - S.Kanageswari d/o Suppiah Shanmugam; Ong, Saw Lan (penerbit ukm, 2013)
Language being a measure of test construct inhibits limited English proficiency (LEP) students’ performance. This study examined the effects of using bilingual (English and Malay) and English-only test booklets among Malaysian LEP students. Their mathematics achievement was investigated by examining the equivalence of the two test booklets by linking the scores using RAGE-RGEQUATE Version 3.22. The 2,021 students came from 34 schools from the states of Penang and Perak. 1049 sat for the bilingual test while 972 for the English-only test which were spirally administered using random group design. Both booklets contain the same 40 multiple-choice Mathematics items obtained from timss 1999 and 2003 released items. Results indicated that a score difference of one unit between the two tests was due to equating error and therefore the bilingual test was not easier for the LEP students, but helpful as they still used the adapted language version to ease understanding. However, they still preferred to answer in English as they were more familiar with the mathematical terminologies that were used. A better alternative is to simplify the linguistic complexity so that language of instruction matched language of assessment.